Clonagem e expressão do gene da toxina beta de Clostridium perfringens tipo B e sua aplicação na imunização de animais - Marcelle Oliveira de Almeida (2010)
The beta toxin produced by Clostridium perfringens types B and C is linked to enterotoxemia that affect humans and animals, mainly goats, cattle, horses, pigs and domestic poultry. The illness has acute or superacute profile causing sudden death and great economic losses to livestock. Due to rapid disease progression, treatment measures are ineffective. The control and prevention must be based on appropriate measures for handling and efficient systematic vaccination of the entire herd. Within this context, it is necessary to develop new vaccines against this enterotoxemia. To do so, part of the ORF encodes the beta toxin of Clostridium perfringens type B, obtained from the cpb gene, was cloned into the pCR2.1-TOPO vector and subcloned into the pET-11a expression vector. The Escherichia coli strain BL21 DE3 was used for expression in a large scale. After the purification step, the protein quantification by Bradford method allowed the estimation of its concentration of approximately 0.3 mg/mL in the soluble fraction and 5 mg/mL in the insoluble fraction (inclusion bodies). The lethality test in mice showed that the recombinant toxin was expressed in the form of toxoid, it release additional steps of inactivation of the toxin to immunize animals. Analysis by Western blotting with anti-beta native antibodies and ELISA with anti-beta recombinant antibodies - both produced in rabbits - showed that the toxoid has antigenic and immunogenic similarity in comparasion to the native toxin. These data demonstrate the use of inclusion bodies for the efficient production of antibodies. Faced with various inefficient national clostridial vaccines available in Brazil, the results presented in this study show that the recombinant beta toxin is a strong candidate for the production of a recombinant polyvalent vaccine against enterotoxemia caused by Clostridium perfringens. .